Research trends and hotspots of circulating tumor DNA in colorectal cancer: a bibliometric study - Zhang, Lele; Zhang, Yuzhe; Chen, Lei; Wang, Xu; Liu, Yulian; Huang, Yishan; Song, Yu; Zhang, Ye; Tai, Jiandong (Frontiers in Oncology, 2025)
IntroductionColorectal cancer (CRC) is the third most common cancer worldwide and the second leading cause of cancer-related deaths. The current standard of care for patients with early-stage CRC includes surgical resection and, in selected patients, adjuvant chemotherapy. Circulating tumor DNA (ctDNA) testing is an important component of liquid biopsy, and with the development of testing technology, its value for clinical application has attracted widespread attention. The aim of this study was to help researchers review what has been achieved and better understand the direction of future research through bibliometric analysis.MethodsWe used the Web of Science Core Collection database to search for ctDNA in CRC-related articles published between 2014 - 2023. Bibliometric analyses of major keywords, authors, countries, institutions, literature and journals in the field were performed using CiteSpace and VOSviewer.ResultsThe number of publications in the field has continued to increase over the last decade. The United States has the highest number of publications, and Italian research scholars have made outstanding contributions. Cancers is the journal with the highest number of publications.ConclusionThis study systematically summarizes the research findings in the field of ctDNA in CRC from 2014 to 2023 and describes the research hotspots and trends worldwide that can guide future research.